Isolates and their Antibiogram in Different Samples from a Tertiary Care Hospital, Kathmandu. - Bhatta, Bibek; Thapa, Roshina; Shahi, Sanjay; Karki, Sushil; Bhatta, Yogesh; Das, Jay Kumar; Pandeya, Dipendra Raj (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: The emergence and spread of antimicrobial resistance constitutes a major risk for human health by limiting the success of these agents in the therapy. The widespread uses of antibiotics, together with the length of time over which they have been available, have led to major problems of resistant organisms contributing to morbidity and mortality. Knowledge of etiological agent and its sensitivities to available drugs is of immense value to the rational selection and use of antimicrobial agents and to the development of appropriate prescribing policies. The aim of this study was to prepare a local antibiogram of the commonly isolated organism at a tertiary care hospital. Methods: A prospective study was conducted at KMC Teaching Hospital, from April 14th to 17th September 2014. Laboratory data of culture and sensitivity were collected from hospital Microbiology Laboratory and analyzed using SPSS software. Results: In our study most of the isolates were Gram negative with Klebsiella Spp. and Escherichia coli being predominant with many MDR isolates. The isolates were found to be resistant to different groups of drugs. We found least resistance to Chloramphenicol, Imepenem and Amikacin. Most of the resistance was found against Amoxicillin and Erythromycin. Among gram positive S. aureus was predominant with 64.7% MRSA and 23.1% VRSA isolates. Conclusions: The most sensitive drug for gram positive was Chloramphenicol, Cephotaxim and Norfloxacine. The only drug which was 100% sensitive to Gram Negative organism was Chloramphenicol.